Gyrification patterns in first-episode, drug-naïve major depression: Associations with plasma levels of brain-derived neurotrophic factor and psychiatric symptoms - Natsuyama, Tomoya; Okamoto, Naomichi; Watanabe, Keita; Chibaatar, Enkhmurun; Tesen, Hirofumi; Hayasaki, Gaku; Ikenouchi, Atsuko; Kakeda, Shingo; Yoshimura, Reiji (Frontiers in Psychiatry, 2023)
Cortical structural changes in major depressive disorder (MDD) are usually studied using a voxel-based morphometry approach to delineate the cortical gray matter volume. Gray matter volume includes information on cortical thickness, surface area, and cortical folding. This study not only compared gyrification patterns in first-episode, drug-naïve patients with MDD to healthy controls (HC) but also examined the association between gyrification patterns and depressive symptoms in MDD patients. Moreover, we investigated the relationship between gyrification patterns and brain-derived neurotrophic factor (BDNF) plasma levels in both groups. The differences in the patterns of brain gyrification between the patients with MDD and HC showed several disease-differentiating factors of gyrification based on the important features (S-Plot and VIP scores). Based on the S-Plot and VIP scores, we identified several types of gyrification factors that cause differences in the disease. We found a statistically significant positive correlation (β= 0.241, 95 % CI: 1.579×10^-4 ~ 4.833×10^-1, p= 0.049) between rG_temp_sup-Plan_polar and the HAM-D total scores. Neither group found no statistically significant correlations between the top 20 disease-generating features and plasma BDNF levels. We found a statistically significant positive correlation (β= 0.241, 95 % CI: 1.579×10^-4 ~ 4.833×10^-1, p= 0.049) between rG_temp_sup-Plan_polar and HAM-D total scores. These results suggest that abnormal early cortical neurodevelopment may mediate vulnerability to MDD, independent of serum BDNF levels.